Highly clientoriented breeding with farmer participation in the Ethiopian cereal tef (Eragrostis tef (Zucc.) Trotter) - Belay, G.; Tefera, H.; Getachew, A.; Assefa, K.; Metaferia, G. (2008)
This paper describes a highly client-oriented breeding applied to enhance the development and release of a tef (Eragrostis tef) variety with farmer participation in Ethiopia. The main features include; clear objective, target cross, early-stage researcher selection, multi-location yield trial, farmer on-station selection, judicious selection of few candidate varieties based on farmers' and researchers' selections, farmer managed on-farm trials, and release through the existing formal procedure. In the application of this strategy, tef exemplifies a crop with local importance, a clear market-driven selection criterion (cash crop) and farmers have better judgment of the criterion than researchers. Using farmers' consistent selection of genotypes, in conjunction with the required quantifiable data, breeders were able to release a new tef variety named "Quncho". The new variety was not the highest yielder, but it was higher in grain yield and better in seed-color quality (very white seed-color) than the long-time cultivated variety DZ-01-196 (Magna), which was used as quality check. Given the appropriate degree of client-orientation, the results also show how farmer participation and formal breeding programs complement each other so as to overcome the rather prohibitive variety release procedures based on data from participatory breeding alone.